2020
DOI: 10.1159/000505584
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Sleep Endoscopy: Evaluation of a Selection Tool for Treatment Modalities for Obstructive Sleep Apnea

Abstract: Obstructive sleep apnea (OSA) is a very common disorder with important day and nighttime symptoms and long-term effects on health. Different treatment modalities such as positive airway pressure (PAP), oral appliance therapy using custom-made, titratable mandibular advancement devices (MAD), different types of surgery and positional therapy have been introduced over the years, with patient preference and adherence to therapy being key elements in improving treatment outcomes. Several patient selection tools to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 83 publications
0
19
0
Order By: Relevance
“…5 Many studies have been published describing patterns of obstruction observed during DISE and associations with baseline OSA severity. 6-9 In addition, there is a growing body of literature describing the impact of DISE on treatment decision making in adult OSA 10-13 and the utility of DISE in predicting surgical outcomes. 14-17…”
mentioning
confidence: 99%
“…5 Many studies have been published describing patterns of obstruction observed during DISE and associations with baseline OSA severity. 6-9 In addition, there is a growing body of literature describing the impact of DISE on treatment decision making in adult OSA 10-13 and the utility of DISE in predicting surgical outcomes. 14-17…”
mentioning
confidence: 99%
“…In the literature [21,22], it is well reported how DISE can provide a good indication of the chances of success with MAD therapy. For many authors [23,24], DISE is a valid diagnostic and prognostic exam, but it has many limitations:…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that for some patients, the NAS worked as well as the OAs. Therefore, we propose that the NAS could be a potential treatment choice for patients with OSAS, because it is important to optimize treatment by trying and combining various methods [33].…”
Section: Discussionmentioning
confidence: 99%